Turner syndrome: French National Diagnosis and Care Protocol (NDCP; National Diagnosis and Care Protocol) - Elodie Fiot; Bertille Alauze; Bruno Donadille; Dinane Samara-Boustani; Muriel Houang; Gianpaolo De Filippo; Anne Bachelot; Clemence Delcour; Constance Beyler; Emilie Bois; Emmanuelle Bourrat; Emmanuel Bui Quoc; et al. (Orphanet Journal of Rare Diseases, 2022)
Abstract Turner syndrome (TS; ORPHA 881) is a rare condition in which all or part of one X chromosome is absent from some or all cells. It affects approximately one in every 1/2500 liveborn girls. The most frequently observed karyotypes are 45,X (40–50%) and the 45,X/46,XX mosaic karyotype (15–25%). Karyotypes with an X isochromosome (45,X/46,isoXq or 45,X/46,isoXp), a Y chromosome, X ring chromosome or deletions of the X chromosome are less frequent. The objective of the French National Diagnosis and Care Protocol (PNDS; Protocole National de Diagnostic et de Soins) is to provide health professionals with information about the optimal management and care for patients, based on a critical literature review and multidisciplinary expert consensus. The PNDS, written by members of the French National Reference Center for Rare Growth and Developmental Endocrine disorders, is available from the French Health Authority website. Turner Syndrome is associated with several phenotypic conditions and a higher risk of comorbidity. The most frequently reported features are growth retardation with short adult stature and gonadal dysgenesis. TS may be associated with various congenital (heart and kidney) or acquired diseases (autoimmune thyroid disease, celiac disease, hearing loss, overweight/obesity, glucose intolerance/type 2 diabetes, dyslipidemia, cardiovascular complications and liver dysfunction). Most of the clinical traits of TS are due to the haploinsufficiency of various genes on the X chromosome, particularly those in the pseudoautosomal regions (PAR 1 and PAR 2), which normally escape the physiological process of X inactivation, although other regions may also be implicated. The management of patients with TS requires collaboration between several healthcare providers. The attending physician, in collaboration with the national care network, will ensure that the patient receives optimal care through regular follow-up and screening. The various elements of this PNDS are designed to provide such support.